Volitional Control of Piloerection: Objective Evidence and Its Potential Utility in Neuroscience Research - Katahira, Kenji; Kawakami, Ai; Tomita, Akitoshi; Nagata, Noriko (Frontiers in Neuroscience, 2020)
The volitional control of piloerection has been previously reported in a small subset of individuals. Although this ability may be useful to study the mechanism underlying piloerection, there is little existing research on this ability, neither objective evidence at a group-level, nor information about its stability under experimental constraints. The present study aimed to validate existing findings of voluntarily generated piloerection (VGP) and to examine its potential contribution to neuroscientific research based on objective evidence of this ability. In Study 1, to confirm the characteristics of VGP reported in previous studies and identify individuals with VGP capability, an online survey of VGP candidates was conducted. In Study 2, 18 VGP holders participated in a mail-based piloerection measurement experiment, and the nature of VGP was examined based on the objective data obtained by image-based analysis (GooseLab). Study 1 largely confirmed the characteristics of VGP reported in previous studies, and Study 2 demonstrated VGP at a group-level and provided information about the temporal characteristics of this ability, which supports the utility of VGP in neuroscientific research. For some participants, VGP appeared to be emotionally promoted, which suggests that VGP has some relationship with the emotional nature of involuntary piloerection. The findings from these studies demonstrate the possible contribution of VGP to elucidating the mechanism of involuntary emotional piloerection and the neural basis of piloerection itself.